English Pronunciation Problems among Indonesian Students of English as a Foreign Language at University Level: A Descriptive Analysis - Reskiawan, Bimas; Abin, Rais; Riyani, Nasmah (Universitas Pahlawan Tuanku Tambusai, 2026)
English pronunciation plays a crucial role in oral communication, particularly in EFL contexts where intelligibility determines communicative success. However, despite years of instruction, many Indonesian university students continue to experience difficulties in producing accurate English sounds. This study aims to analyze English pronunciation problems faced by fifth semester Indonesian EFL university students at Universitas Sembilanbelas November Kolaka. A descriptive quantitative design was employed involving thirty students selected through purposive sampling. Data were collected using a pronunciation test in the form of word list and sentence reading tasks and analyzed using frequency and percentage. The findings reveal that vowel-related errors were the most dominant, particularly in distinguishing long and short vowels, followed by consonant errors such as interdental fricatives and consonant cluster simplification. These difficulties are mainly influenced by first language interference and phonological differences between Bahasa Indonesia and English. The study highlights the need for explicit and systematic pronunciation instruction to improve students’ spoken intelligibility.